Body and mind? Exploring physiological and psychological factors to explain endurance performance in cycling - Röthlin, P.; Wyler, M.; Müller, B.; Zenger, N.; Kellenberger, K.; Wehrlin, J. P.; Birrer, D.; Lorenzetti, S.; Trösch, S. (European Journal of Sport Science, 2023)
Endurance athletes attribute performance not only to physiological factors, but also refer to psychological factors such as motivation. The goal of this study was to quantify the proportion of the variance in endurance performance that is explained by psychological factors in addition to the physiological factor VO2max. Twenty-five athletes of the U17 Swiss Cycling national team (7f, 18 m, 15.3 ± 0.5 years) were examined in a cross-sectional study with psychological factors and VO2max as independent variables and endurance performance in road cycling as dependent variable. Questionnaires were used to assess psychological factors (i.e. use of mental techniques, self-compassion, mental toughness, achievement motivation, and action vs. state orientation). VO2max was measured by a step incremental cycle ergometer test of exhaustion. Endurance performance was measured in a cycling mountain time trial (1,320 m long, incline of 546 meters). A multiple regression model was created by using forward selection of regression model predictors. Results showed that higher VO2max values (ß = .48), being male (ß = .26), and higher achievement motivation (i.e. perseverance, ß = .11) were associated with a better endurance performance. A more frequent use of one particular mental technique (i.e. relaxation techniques, ß = .03) was associated with a worse endurance performance. Our study shows that a physiological factor like VO2max explains endurance performance to a large extent but psychological factors account for additional variance. In particular, one aspect of achievement motivation, namely perseverance, was associated with a better endurance performance.